EXPLORING AMYLASE ACTIVITY IN BACTERIA ISOLATED FROM CEREAL - INFESTING INSECTS: A MICROBIOLOGICAL APPROACH - Thakare, Dattabhushan Karvir; Hamde, V.S.; Narsinge, A.P.; Kadam, Aditya S.; Dixit, Ankita M. (Journal of Global Pharma Technology, 2024)
Amylases are significant industrial enzymes with diverse applications across various industries. This study aimed to isolate and screening of amylase-producing microorganisms from the gut and salivary gland microflora of cereal-spoiling insects. Samples were collected from cereals infested by pests such as the lesser grain borer, Granary weevil, Rice weevil, and Angoumois grain moth in the Beed district. The digestive tracts of the third and fifth instar larvae of Sitophilus granarius were dissected, homogenized, and serially diluted. The dilutions were spread on nutrient and starch agar plates and incubated to isolate gut flora. Bacterial isolates were tested for amylolytic activity using the starch hydrolysis test. Among the isolates, one coded as SG6 demonstrated the highest amylolytic activity with a 3 mm zone of clearance on starch agar plates. Morphological and Gram staining analysis identified the isolate as gram-positive and rod-shaped. The clear zones observed around the colony indicate starch hydrolysis by amylase production. The colony characteristics of isolate SG6 were circular, medium-sized, and white, with smooth edges, raised elevation, no pigmentation, and motile nature. This study confirms the presence of amylase-producing bacteria in the gut microflora of cereal-spoiling insects and highlights the potential of isolating SG6 for industrial applications. Keywords: Amylase production, Cereal-spoiling insects, Gut microflora, Starch hydrolysis, Sitophilus granaries.